2021
DOI: 10.2478/aucft-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic Extracts from Agro-Industrial Co-Products Enhance Oxidative Stability of Candelilla Wax or Celluloses Derivatives Oleogels

Abstract: Ethanol oleoresins obtained from orange peel, pea pod, or pomegranate peel were employed to enrich soybean oil before elaborating two types of oleogels, one made with candelilla wax, another made with a mixture of celluloses derivatives, in order to determine their effect on oleogel oxidative stability. Orange peel oleoresin obtained a higher amount of polyphenols as catechol acid equivalent (9.09 meq/g), as compared to pea pod oleoresin or pomegranate peel (8.80 and 8.55, respectively), although pomegranate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…The cooling profile in all the samples except Sy5 peaked at ~40 °C (T c ), indicating the major role of n-alkanes in guiding the crystallization. A similar crystallization peak has been observed for oleogels prepared by using CW in soybean oil [ 62 ]. Although few studies have reported the role of vegetable oil in maintaining the melting and crystallization temperature [ 63 ], it is quite possible that the wax has more influence on the thermal properties of the oleogels.…”
Section: Resultssupporting
confidence: 74%
“…The cooling profile in all the samples except Sy5 peaked at ~40 °C (T c ), indicating the major role of n-alkanes in guiding the crystallization. A similar crystallization peak has been observed for oleogels prepared by using CW in soybean oil [ 62 ]. Although few studies have reported the role of vegetable oil in maintaining the melting and crystallization temperature [ 63 ], it is quite possible that the wax has more influence on the thermal properties of the oleogels.…”
Section: Resultssupporting
confidence: 74%